Energy optimization of 6T SRAM cell using low-voltage and high-performance inverter structures - M. Madhusudhan Reddy; M. Sailaja; K. Babulu (International Journal of Electrical and Computer Engineering (IJECE), 2019)
The performance of the cell deteriorates, when static random access memory (SRAM) cell is operated below 1V supply voltage with continuous scale down of the complementary metal oxide semiconductor (CMOS) technology. The conventional 6T, 8T-SRAM cells suffer writeability and read static noise margins (SNM) at low-voltages leads to degradation of cell stability. To improve the cell stability and reduce the dynamic power dissipation at low- voltages of the SRAM cell, we proposed four SRAM cells based on inverter structures with less energy consumption using voltage divider bias current sink/source inverter and NOR/NAND gate using a pseudo-nMOS inverter. The design and implementation of SRAM cell using proposed inverter structures are compared with standard 6T, 8T and ST-11T SRAM cells for different supply voltages at 22-nm CMOS technology exhibit better performance of the cell. The read/write static noise margin of the cell significantly increases due to voltage divider bias network built with larger cell-ratio during read path. The load capacitance of the cell is reduced with minimized switching transitions of the devices during high-to-low and low- to-high of the pull-up and pull-down networks from VDD to ground leads to on an average 54% of dynamic power consumption. When compared with the existing ones, the read/write power of the proposed cells is reduced to 30%. The static power gets reduced by 24% due to stacking of transistors takes place in the proposed SRAM cells as compare to existing ones. The layout of the proposed cells is drawn at a 45-nm technology, and occupies an area of 1.5 times greater and 1.8 times greater as compared with 6T-SRAM cell.